The MRI-Linear Accelerator Consortium: Evidence-Based Clinical Introduction of an Innovation in Radiation Oncology Connecting Researchers, Methodology, Data Collection, Quality Assurance, and Technical Development - Kerkmeijer, Linda G. W.; Fuller, Clifton D.; Verkooijen, Helena M.; Verheij, Marcel; Choudhury, Ananya; Harrington, Kevin J.; Schultz, Chris; Sahgal, Arjun; Frank, Steven J.; Goldwein, Joel; Brown, Kevin J.; Minsky, Bruce D.; et al. (Frontiers in Oncology, 2016)
An international research consortium has been formed to facilitate evidence-based introduction of MR-guided radiotherapy (MR-linac) and to address how the MR-linac could be used to achieve an optimized radiation treatment approach to improve patients’ survival, local, and regional tumor control and quality of life. The present paper describes the organizational structure of the clinical part of the MR-linac consortium. Furthermore, it elucidates why collaboration on this large project is necessary, and how a central data registry program will be implemented.